Breakdown data generation and in-die deconvolution methodology to address BEOL and MOL dielectric breakdown challenges. Issue 12 (December 2015) - Chen, F.; Graas, Carole; Shinosky, Michael; Zhao, Kai; Narasimha, Shreesh; Liu, Xiao Hu; Tian, Chunyan
Abstract: Both middle-of-line (MOL) gate to contact spacer dielectric and back-end-of-line (BEOL) low- k dielectric breakdown data are commonly convoluted with multiple variables induced by process steps such as lithography, etch, chemical–mechanical polish (CMP), cleaning, and thin film deposition. The traditional method of stressing one device under test (DUT) per die or multiple DUTs per die, without careful data deconvolution, is incapable of addressing current complex MOL PC-CA and BEOL low- k dielectric breakdown modeling challenges. Generally, compound Weibull distributions in various unpredictable shapes induced by various die-to-die variations would be generated and such compound distributions could lead to a wrong low-percentile failure rate projection and a non-Poisson area scaling outcome. In this paper, a generation method plus an analytics procedure to analyze die-to-die variation is proposed to soundly evaluate both MOL and BEOL dielectric time-dependent-dielectric breakdown data. Relying on such die-to-die data generation and analytics, a diagnostic reliability concept is further proposed for comprehensive process diagnostics and more accurate reliability failure rate determination. Highlights: We develop a die-to-die data generation and analysis method to address BEOL low-k and MOL PC-CA dielectric breakdown. We also develop a new failure rate calculation method for a realistic case of shipped dies with different lifetimes. Die-to-die lifetime deconvolution and in-die Weibull slope restoration are essential for reliability assessment. Combining die-to-die reliability data and die-to-die process data, a diagnostic reliability concept is proposed.